2018
DOI: 10.3390/jof4010027
|View full text |Cite
|
Sign up to set email alerts
|

Non-Culture Diagnostics for Invasive Candidiasis: Promise and Unintended Consequences

Abstract: Blood cultures are positive for Candida species in < 50% and < 20% of hematogenously disseminated and intra-abdominal candidiasis, respectively. Non-culture tests such as mannan, anti-mannan antibody, Candida albicans germ tube antibody (CAGTA), 1,3-β-d-glucan (BDG), the T2Candida nanodiagnostic panel, and polymerase chain reaction (PCR) are available for clinical use, but their roles in patient care are uncertain. Sensitivity/specificity of combined mannan/anti-mannan, BDG, T2Candida and PCR for candidemia ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 45 publications
(61 reference statements)
3
80
0
2
Order By: Relevance
“…PCR performance data for forms of IC other than candidemia are relatively limited -for intra-abdominal candidiasis, PCR sensitivities of 86-91% have been reported for the species targeted, but specificity varies widely (33-97%) Fortún et al, 2014;León et al, 2016;Clancy and Nguyen, 2018b). Nguyen et al (2012) found a Candida real-time PCR assay to be more sensitive than the Fungitell R 1,3-β-D glucan (BDG) assay (Associates of Cape Cod, United States) for diagnosis of all IC (80 versus 56%) as well as deep seated (blood culture negative) candidiasis (89 versus 53%).…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
See 1 more Smart Citation
“…PCR performance data for forms of IC other than candidemia are relatively limited -for intra-abdominal candidiasis, PCR sensitivities of 86-91% have been reported for the species targeted, but specificity varies widely (33-97%) Fortún et al, 2014;León et al, 2016;Clancy and Nguyen, 2018b). Nguyen et al (2012) found a Candida real-time PCR assay to be more sensitive than the Fungitell R 1,3-β-D glucan (BDG) assay (Associates of Cape Cod, United States) for diagnosis of all IC (80 versus 56%) as well as deep seated (blood culture negative) candidiasis (89 versus 53%).…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
“…Many of these assays remain investigational as they have not been validated for diagnosing IC in multi-center studies, nor is there evidence that any one commercial test is superior. The choice of adopting an in house rather than commercial assay is dependent upon workflow and capacity in individual testing laboratories and cost (Clancy and Nguyen, 2018b), and results should be considered with caution. To date, the T2Candida panel and the T2Dx instrument (T2 Biosystems, United States) is the only platform approved by the US Food and Drug Administration (FDA) to detect Candida spp.…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
“…[22][23][24] New diagnostic methods for the timely identification of IFD have emerged in recent years and are summarized in Table 3. [22][23][24][25][26][27][28] An ideal diagnostic test would be minimally invasive, have a rapid turnaround time to result, be both sensitive and specific for the diagnosis of IFD, differentiate between colonization and invasive disease, and yield speciation and susceptibility data. Clinical trials focused on new diagnostic methods or improvements of existing methods that are currently underway are described in Table 4.…”
Section: Identification and Management Of At-risk Patientsmentioning
confidence: 99%
“…23 The detection of C albicans, C parapsilosis, and C glabrata infections by C albicans germ tube antibody involves use of an indirect immunofluorescence assay against a protein expressed during tissue invasion and biofilm formation, thereby offering potentially useful information in differentiating between infection and colonization. 23,26 Although clinical studies of PCR have used a multitude of platforms and targets, it has generally performed well but is relatively high-cost and labor-intensive. 23,25 A recent development in the diagnosis of C albicans, C tropicalis, C glabrata, Candida krusei, and Candida parapsilosis infections is the T2Candida panel using T2MR technology, which enables the detection of specific molecular targets using magnetic resonance.…”
Section: Identification and Management Of At-risk Patientsmentioning
confidence: 99%
See 1 more Smart Citation